The profitability and distance to distress of European banks: do business choices matter? - Marques, Bernardo P. (2022)
This paper examines which business choices are more likely to increase the profitability and distance to distress of banks, and whether changing business model pays off. We find that the profitability and distance to distress increase with the use of customer deposits and equity, and decrease with size; also, the top performers tend to have a high relationship banking orientation and/or operate a retail focused business model. Furthermore, we document that income diversification only bears a positive impact on the distance to distress of banks highly focused on relationship banking, and size only bears a negative effect on the profitability of these banks as well; additionally, only banks with a low relationship banking orientation significantly benefit from customer deposits. With respect to the effects of business model changes, we find that shifts from the retail diversified funding model to either the retail focused or the large diversified models improve profitability in the medium term. Finally, we find evidence that large diversified banks benefited from internal capital markets during the twin financial crisis by tapping into low-cost funding from subsidiaries. Our results are robust to changes to our baseline model that account for endogeneity and persistency issues.